Vulnerability and costs of adaptation strategies for housing subjected to flood risks: Application to La Guérinière France. (July 2020) - Creach, Axel; Bastidas-Arteaga, Emilio; Pardo, Sophie; Mercier, Denis
Abstract: Coastal flooding along the Atlantic coast caused by Storm Xynthia killed 41 people. The location and configuration of residential housing were the main factors affecting the vulnerability of people to flooding. The French government responded by destroying buildings in the most flood-prone areas and relocating residents to safer areas. This strategy attracted much criticism, in particular because of the high costs involved with demolition on this scale, and that not insufficient consideration was given to other possible solutions. In this study, the goal is to compare different adaptation strategies in terms of cost of implementation and efficiency in order to reduce the vulnerability of houses to flooding. The strategies are grouped based on: (i) protection, (ii) relocation, (iii) housing architectural adaptation, and (iv) preventive warning and evacuation. This work is applied to La Guérinière, an Atlantic coastal town at risk of coastal flooding, although it was not impacted by Storm Xynthia. The initial results show that the most efficient strategy to reduce housing vulnerability to coastal flooding is also the most expensive. Ranked from the most to the least efficient and expensive, the strategies are as follows: (i) relocation, (ii) housing architectural adaptation, (iii) protection, (iv) and preventive warning and evacuation. Until now, these strategies have been limited as they omit human behaviour in response to coastal flooding scenarios. Therefore, this study examines the role of human behaviour in relation to different mitigative strategies. The efficiency and costs of the strategies are then reappraised.